2013
DOI: 10.5923/j.cmaterials.20130306.04
|View full text |Cite
|
Sign up to set email alerts
|

Quality Control in Plywood Manufacturing: Physical Properties of Commercial Plywood of Pinus sp

Abstract: Wood of genus Pinus have been widely used by plywood Brazilian industry, motivated by their good physical and mechanical properties as well as reforestation policies. For p lywood companies, quality control for its commercialization presents itself as essential. In th is sense, this paper aims to evaluate, by means of physical properties, homogeneity of plywood manufacturing process using Pinus sp. So, we selected four panels, and extracted samples to obtain their physical properties. Analysis of variance (ANO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
(8 reference statements)
0
0
1
Order By: Relevance
“…Pinus plywood may present water absorption close to 60% (Almeida et al, 2013;Silva et al, 2012;Campos et al, 2009), lower than those observed in this study. This difference is due to low wood density of both species used and the veneer thickness of 2.2 mm.…”
Section: Panel Physical Propertiescontrasting
confidence: 69%
“…Pinus plywood may present water absorption close to 60% (Almeida et al, 2013;Silva et al, 2012;Campos et al, 2009), lower than those observed in this study. This difference is due to low wood density of both species used and the veneer thickness of 2.2 mm.…”
Section: Panel Physical Propertiescontrasting
confidence: 69%